Childhood Physical Maltreatment and Young Adult Dating Violence: A Propensity Matching Approach. Issue 22 (November 2017) - Tomsich, Elizabeth; Jennings, Wesley G.; Richards, Tara N.; Gover, Angela R.; Powers, Ráchael A.
Intimate partner violence disproportionately occurs among young adults and relates to a range of health and behavioral problems throughout the life course. Although numerous studies substantiate the prevailing cycle of violence perspective, methodological limitations in prior research prohibit the conclusion of a causal relationship between childhood physical maltreatment and dating violence perpetration and victimization in young adulthood. The current research applies a quasi-experimental propensity score matching approach to a large sample of young adults ( n = 4, 168) to isolate the causal effect of childhood physical maltreatment on dating violence perpetration and victimization. Results suggest selection bias accounts for the correlation between childhood physical maltreatment and young adult physical dating violence perpetration and victimization, indicating a spurious relationship—before matching: odds ratio (OR) = 1.38, p < .001; OR = 1.35, p < .001; after matching: OR = 1.08; p = .379; OR = 1.09; p = .297. Study limitations and implications are discussed.